Therapeutic delivery of RNAi - Lu, Patrick (Henry Stewart Talks, 2007)
RNAi therapeutics development, RNAi cellular activity, In vivo siRNA delivery is key, Clinically viable siRNA deliveries, Local delivery of siRNA, Gene silencing in tumors, Cancer target validation in vivo, RNAi effects in mouse brain, joints, eyes and lungs, siRNA therapeutics in primate models, Challenges to siRNA systemic delivery, Systemic delivery technology, Targeted nanoparticle siRNA delivery, Self assembled nanoparticle, Integrin av-beta is a validated target, Dual-targeted therapeutic approach, Neovasculature targeting siRNA, Multi-targeted anti-angiogenesis, Efficient targeted systemic delivery, Systemic siRNA delivery to eyes, Systemic siRNA delivery for neuroblastoma treatment, Tumor neovasculature inhibition, siRNA/Atelocollagen anti-tumor efficacy, Transferrin-mediated systemic delivery, Antibody-mediated tumor targeting, Targeted anti-HBV activity, RNAi effect of chol-siRNA, PEI-mediated siRNA lung targeting, Clinicallyviable delivery is the key for successful siRNA therapeutics
Archived at 2021/02/25